FIQH AL-HADTS: PERSPEKTIF HISTORIS DAN METODOLOGIS - Saifuddin, Saifuddin (Jurnal Ilmiah Ilmu Ushuluddin, 2012)
Study of fiqh hadith Sharh Hadith is one of interested topic to discuss. Study of fiqhal-Hadith is a multidisciplinary field of study that involves almost all branches ofhadith disciplines, involving sanad sciences, Rijal al-Hadith sciences, as well as matnsciences. The science is in its infancy still simple, then grow gradually and extends tobecome an independent branch of science known as Sharh Hadith al-hadith or fiqh.